BURUH DI PERKEBUNAN SAWIT RAKYAT DI DESA SUMBER MULYA 1993-2011 - Setya Putra, Siti Heidi Karmela (Universitas Batanghari Jambi, 2017)
Abstract The purpose of this research is to describe the economic activity and the role of the workers in the palm plantations in Desa Sumber Mulya and explain the economic life of the workers result of the influence of the economic activities of the people's palm plantations. The research method used is historical method, which is a process of testing and critically analyzing past events, with stages starting from heuristics, criticism, interpretation, historiography. The approach used is a multidisciplinary theoretical approach by applying other social sciences concepts such as economics and sociology. . The results showed that the community palm plantations in Desa Sumber Mulya show progressive conditions, one of them in terms of increasing the number of workers and wages of workers every year so as to improve their economic life. Not only have an economic impact on labor, this oil palm plantation also affects the economic condition of the farmers as well as the owners of the palm plantation due to the continued increase in profits.Keywords: palm plantation, Labor, farmer, Sumber Mulya